THE EFFECTIVENESS OF USING THE SUBJECTIVE IN LEARNING (SIL) LEARNING MODEL IN IMPROVING THE UNDERSTANDING OF NATURE OF SCIENCE (NoS) SUBJECTIVE ASPECTS IN ELEMENTARY SCHOOL STUDENTS - Udin Syaefudin Sa’ud; Ari Widodo; Siti Nurkamilah (Universitas Majalengka, 2024)
Understanding the Nature of Science (NoS) is essential because it helps students appreciate, understand and criticize science more effectively. The subjective aspect, which is one aspect of the Nature of Science (NoS), still needs to be better understood among elementary school students. This Research discusses the effectiveness of using the Subjective In Learning (SIL) learning model in increasing understanding of the Nature of Science (N0S). ) subjective aspects of elementary school students. This Research was conducted using a quantitative approach, a pre-experimental research type with a one-group pretest post-test design. The instruments used were questionnaires and interviews. The research location is at a leading private elementary school in Garut Regency, West Java. Based on the Research that has been carried out, the results show that the Subjectivies in Learning (SIL) learning model is effective in increasing students' understanding of the subjective aspect of the Nature of Science (NoS), with an increase of 0.34, which can be included in the medium category. The author recommends that further researchers develop other learning models to increase students' understanding of different aspects of NoS.